The impact of physical exercise on the endocrine system in men: A review - Marina A. Berkovskaya; Asya A. Elmurzaeva; Api L.-A. Edaev; Timerlan Yu. Selakhov; Habib M. Tokaev; Irina D. Gurova (Consilium Medicum, 2024)
The endocrine system regulates many functions of the human body to maintain optimal performance and homeostasis of various organs and systems. Playing sports and various physical activities changes the regulatory function of the endocrine organs in the form of successive phases, and the magnitude of the response depends on the intensity and duration of the physical stress exerted. Hormonal regulation during physical activity facilitates the adaptation of the functional activity of the cardiovascular system, the activation of energy depots, and the maintenance of adequate tissue hydration. Physical activity leads to an increase in the production of growth hormone, insulin-like growth factor-1, total and free testosterone, which enhances the anabolic reactions of the body. It is important to understand the relationship and impact of physical activity on the functioning of the endocrine system for the development of physical exercise’s complexes, patient rehabilitation, research and treatment of endocrine disorders. The effect of physical activity on the endocrine system for women has been studied to a greater extent, in contrast to men, where the data is contradictory. Therefore, in this article we will highlight the features of various endocrine organs and hormones during sports activities in men.